Feline oral squamous cell carcinoma: recent advances and future perspectives - Tutu, Paul; Daraban Bocaneti, Florentina; Altamura, Gennaro; Dascalu, Mihaela Anca; Horodincu, Loredana; Soreanu, Octavian Dumitru; Tanase, Oana Irina; Borzacchiello, Giuseppe; Mares, Mihai (Frontiers in Veterinary Science, 2025)
Feline oral squamous cell carcinoma (FOSCC) is the most common oral malignancy in cats, characterized by aggressive local invasion, high metastatic potential, and poor clinical outcomes. Its etiology is multifactorial, involving genetic mutations (notably TP53), viral infections (such as papillomavirus), environmental exposures to xenobiotics and chronic oral inflammation, though definitive causal relationships remain unclear due to limited studies. FOSCC primarily affects older, non-pedigree cats, with no clear sex or breed predisposition, and most frequently arises in the gingiva, sublingual region, and tongue. FOSCC presents with non-specific signs like weight loss, oral ulceration, and difficult eating, often leading to late diagnosis. FOSCC displays highly infiltrative growth with marked cellular pleomorphism and frequent bone invasion. Recent advances have identified various biomarkers, such as Ki-67, Cyclin D1, Bmi-1, and EMT-related proteins, that enhance diagnostic accuracy and prognostic assessment, while emerging research into tumor mutational burden and metabolic pathways offers promising therapeutic targets. Prognosis remains poor, with median survival times typically under 2 months and limited response to conventional treatments; however, surgical intervention and novel targeted therapies show potential for improved outcomes. This review synthesizes recent progress in understanding FOSCC etiology, pathology, and therapeutic strategies, and highlights ongoing challenges and future directions in the management of this devastating feline cancer.